Phenanthrene‐Fused‐Quinoxaline as a Key Building Block for Highly Efficient and Stable Sensitizers in Copper‐Electrolyte‐Based Dye‐Sensitized Solar Cells. (2nd April 2020) - Jiang, Huiyun; Ren, Yameng; Zhang, Weiwei; Wu, Yongzhen; Socie, Etienne Christophe; Carlsen, Brian Irving; Moser, Jacques‐E.; Tian, He; Zakeeruddin, Shaik Mohammed; Zhu, Wei‐Hong; Grätzel, Michael
Abstract: Dye‐sensitized solar cells (DSSCs) based on Cu II/I bipyridyl or phenanthroline complexes as redox shuttles have achieved very high open‐circuit voltages ( V OC, more than 1 V). However, their short‐circuit photocurrent density ( J SC ) has remained modest. Increasing the J SC is expected to extend the spectral response of sensitizers to the red or NIR region while maintaining efficient electron injection in the mesoscopic TiO2 film and fast regeneration by the Cu I complex. Herein, we report two new D‐A‐π‐A‐featured sensitizers termed HY63 and HY64, which employ benzothiadiazole (BT) or phenanthrene‐fused‐quinoxaline (PFQ), respectively, as the auxiliary electron‐withdrawing acceptor moiety. Despite their very similar energy levels and absorption onsets, HY64 ‐based DSSCs outperform their HY63 counterparts, achieving a power conversion efficiency (PCE) of 12.5 %. PFQ is superior to BT in reducing charge recombination resulting in the near‐quantitative collection of photogenerated charge carriers. Abstract : Phenanthrene‐fused‐quinoxaline (PFQ) is demonstrated as an efficient auxiliary acceptor to realize long‐wavelength response, enhancing the photocurrent as well as power conversion efficiency (PCE) of copper‐electrolyte‐based dye‐sensitized solar cells. The resulting dye, termed HY64, achieves an outstanding PCE of 12.5 %.